The alienated religion studies teacher: a case study in Cape Town, South Africa - Driesen, Danika (Department of Religious Studies, 2017)
South Africa's post-apartheid National Policy on Religion and Education instituted in 2003 ushered in a new paradigm for the study of religion in the country's schools. It promotes a programme of teaching and learning about religious diversity that constitute the nation. While this revised policy enabled Religion Studies educators to grapple with new ways of thinking about the study of religion, it still demanded them to assume a standardised role that focused more on their duties and responsibilities of promoting a multi-religious approach in an impartial manner. This homogenous policy image neglected the teachers' interpretations and reality of the profession. Consequently, a gap emerged between the policy-imagined role and Religion Studies teachers' perspectives. This thesis explores the gap between what the national policy expects from the teachers and their readiness for teaching Religion Studies. Rahel Jaeggi's concept of alienation is used to critically analyse the alienating effects of the national policy images' failure in recognising the realities of the profession. Jaeggi provides a renewed framework on the concept that entails critically analysing an individual's social role in terms of how s/he succeeds or fails to appropriate and identify with it. A case study research of eleven teachers who taught Religion Studies in high schools in Cape Town, South Africa was conducted. The findings reveal that the gap disrupted their roles, and resulted in a 'double' alienation for them. It also shows educators integrating their religious identities into their teaching methods, which enhanced their proficiency at teaching the subject and alleviating their 'double' alienation. The teachers' methodologies demonstrate that they are open enough to approach the aims of Religion Studies, and to approach diversity that is not from the national policy's perspective of a distant secular approach, but rather one that opens their own religious traditions to new ones. I argue that despite the Religion Studies teachers alleviating their 'double' alienation to some extent by integrating their religious identities into their teaching methods, they still remained in a state of alienation due to the post-apartheid government's top-down education strategy.